Działalność naukowa i publicystyczna Edwarda Taylora - Lityńska, Aleksandra (Wydział Prawa i Administracji UAM, 1985)
The article is devoted to one of the most distinguished economists of Poland of the interwar period. The authoress analyses the scientific output of E. Taylor which was produced before the World War two and in the Poples Poland. His contribution to the Polish economic literature is indicated especially in the aspect of studies on statics and economic dynamics. The attention is also drawn to his economic realism in specific matters of economic policies of the Second Republic and to his accurate opinions on monetary policy, currency reform of 1924, and estimation of the crisis of the thirties. A didactic activity of E. Taylor is also presented, he was a founder of the Poznań school of economics and the author of numerous academical textbooks.
Scientific and publicistic activities of Edward Taylor